Effect of periodicstructureson the coursetheinitial and final sectionsaxisymmetric jet - Төлеуов, Ғ.; Қалқанова, М.; Сейдулла, Ж.Қ. (Recent Contributions to Physics, 2016)
This article discusses the effect of the periodic structure on the course of the initial and final sections of ax symmetric jet. It is a question of education of primary vortices and the interaction of the sevorticesin the future. The dependence of the Strouhal number on the Reynolds number. The study found that the mainstream of acoustic disturbances are the structures of discrete vortices, as well as the dependence εu pulsation intensity of the Strouhal number.